1999
DOI: 10.1084/jem.190.8.1115
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Ox40 Function in Cd28-Deficient Mice Is Linked with Failure to Develop Cxc Chemokine Receptor 5–Positive Cd4 Cells and Germinal Centers

Abstract: Mice rendered deficient in CD28 signaling by the soluble competitor, cytotoxic T lymphocyte–associated molecule 4–immunoglobulin G1 fusion protein (CTLA4-Ig), fail to upregulate OX40 expression in vivo or form germinal centers after immunization. This is associated with impaired interleukin 4 production and a lack of CXC chemokine receptor (CXCR)5 on CD4 T cells, a chemokine receptor linked with migration into B follicles. Germinal center formation is restored in CTLA4-Ig transgenic mice by coinjection of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
215
3
7

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 251 publications
(237 citation statements)
references
References 39 publications
12
215
3
7
Order By: Relevance
“…Constitutive expression of OX40L on DCs leads to a CD28-dependent increase in the numbers of CXCR-5 CD4 cells 5, greatly increased numbers of CD4 T cells within B follicles, and large GCs 3. Preliminary analysis of OX40-deficient mice shows the opposite phenotype, with GC formation being reduced (unpublished observations).…”
Section: Role Of Cd28 and Ox40 In Directing Cd4 T Cell Migration To Bmentioning
confidence: 89%
See 2 more Smart Citations
“…Constitutive expression of OX40L on DCs leads to a CD28-dependent increase in the numbers of CXCR-5 CD4 cells 5, greatly increased numbers of CD4 T cells within B follicles, and large GCs 3. Preliminary analysis of OX40-deficient mice shows the opposite phenotype, with GC formation being reduced (unpublished observations).…”
Section: Role Of Cd28 and Ox40 In Directing Cd4 T Cell Migration To Bmentioning
confidence: 89%
“…In contrast, expression of the T cell activation antigen OX40 on naive CD4 T cells is largely CD28 dependent, both in vivo and in vitro 5. Although others have suggested that OX40 expression is CD28 independent 6, these studies looked at total rather than naive CD4 T cell responses.…”
Section: Role Of Ox40 and Cd28 In Priming Cd4 Cells: Rapid Expansion mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell numbers were calculated based on the proportion of viable cells in the lymphocyte gate using, where possible, propidium iodide (0.25 lg/ml) to exclude dead cells. Tissue sections were double-stained for IgD (Binding Site) in combination with either IgM (Serotec), CD3 (KT3; Serotec) or CD4 (GK1.5; Serotec) as described [48].…”
Section: Flow Cytometry and Immunohistologymentioning
confidence: 99%
“…[3][4][5] These were first termed T follicular helper (Tfh) cells by Chtanova et al 6 Germinal centre localized Tfh cells expressed the chemokine receptor CXCR5 as well as costimulatory molecules CD40L 7 and ICOS. 8 IL-21 is required for germinal centre formation for T-cell dependent antigens.…”
Section: What Are Tfh Cellsmentioning
confidence: 99%